Design and preparation of flocculant with self-degrading characteristics for dewatering of oil sand tailings. Issue 11 (1st September 2020) - Wang, Haiwang; Chao, Li; Wei, Xinfang; Qi, Xiwei; Li, Jinlong; Jiang, Luhong; Li, Wenzhe; Jia, Penghui
Abstract: Polymer flocculation technology is widely used in the treatment of oil sand tailings pollutants. However, the most commonly used polyacrylamide flocculants have problems of secondary pollution. In this paper, under ultraviolet light, the composite was prepared by photoinitiated precipitation polymerization of acrylamide on the surface of nano TiO2, providing a facile strategy for the synthesis of organic-inorganic hybrid flocculants. A series of organic-inorganic hybrid materials with different light sources, UV irradiation times, TiO2 contents and AM contents were synthesized, and connected by covalent bonds. In addition, in order to analyze the synthesis mechanism of the composite material, the functional groups of the material were investigated by Fourier transform infrared spectroscopy (FTIR), the morphology and structure were observed by transmission electron microscopy (TEM), and thermodynamic stability was analyzed by thermogravimetry. The flocculation mechanism was studied by testing the zeta potential and GPC spectrum of the organic-inorganic composites. Moreover, the composite material increased the transmittance by 74.33% and decreased the water volume by 84% for simulated oil sand tailings. Ultimately, the degradation experiments showed that the prepared organic-inorganic composite flocculant had nice self-degradation performance, which efficiency could reach over 90% within 2 hours. In conclusion, this material can be employed to enhance the recovery of water from oil sand tailings, also with outstanding degradation characteristics. Graphical Abstract: uf0001